ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN METODE EOQ (ECONOMIC ORDER QUANTITY) PADA PT. DUTA ABADI PRIMANTARA PALEMBANG - Kusminai Armin; Baidowi Abdhie; Bella Dwi Arimbi (Universitas Tridinanti, 2020)
PT. Duta Abadi Primantara Palembang is one of the companies engaged in manufacturing. Which is where the company is serving the market demand for high quality bedding. Thus, the company tries to carry out its operational activities effectively and efficiently, although in practice there are still weaknesses in the control system used by the company. This study uses quantitative analysis techniques in which the data obtained from the field are processed in such a way as to provide systematic, factual, and accurate data regarding the problems studied at the company PT. Duta Abadi Primantara Palembang with the EOQ (Economic Order Quantity) method. So that a conclusion can be drawn.The results showed that based on the determination of raw material control using the Economic Order Quantity (EOQ) method is more optimal and more efficient than the conventional methods set by the company. This can be proven by the availability of optimal raw material purchases and TIC (Total Inventory Cost) savings. In anticipating the shortage of raw material inventory companies should consider using EOQ in raw material procurement policies because by using EOQ, companies can purchase optimal raw materials at a lower cost than company policy. Keywords: Raw Material Inventory Control, Economic Order Quantity.